Degradation of Metal Ions with Electricity Generation by Using Fruit Waste as an Organic Substrate in the Microbial Fuel Cell - Ghada Mohamed Aleid; Anoud Saud Alshammari; Asma D. Alomari; Shehu Sa’ad Abdullahi; Rania Edrees Adam Mohammad; Rokhsana Mohammed Ismail Abdulrahman (International Journal of Chemical Engineering)
A potential and developing green technology for producing renewable energy and treating wastewater is the microbial fuel cell (MFC). Despite several advancements, there are still several serious problems with this approach. In the present work, we addressed the problem of the organic substrate in MFC, which is necessary for the degradation of metal ions in conjunction with the production of energy. The utilization of fruit waste as a carbon source was strongly suggested in earlier research. Hence, the mango peel was used as a substrate in the current study. Within 25 days of operation, a 102-mV voltage was achieved in 13 days, while the degradation efficiency of Cr3+ was 69.21%, Co2+ was 72%, and Ni2+ was 70.11%. The procedure is carried out in the batch mode, and there is no continuous feeding of the organic substrate. In addition, a detailed explanation of the hypothesized mechanism for this investigation is provided, which focuses on the process of metal ion degradation. Lastly, future and concluding remarks are also enclosed.